On the trail with Miss Pace - Denslow, Sharon Phillips; Karas, G. Brian (New York, NY : Simon & Schuster Books for Young Readers, 1995)
Twins Bill and Phil spend an exciting vacation out west at the same ranch as their teacher, Miss Pace, and her boyfriend, the wild cowboy Last Bob.
Keywords: Teachers; Twins; Cowboys